Stretchable and dynamically stable promising two-dimensional thermoelectric materials: ScP and ScAs. Issue 20 (7th May 2019) - Kaur, Kulwinder; Murali, Devaraj; Nanda, B. R. K.
Abstract : We present two newly designed 2D thermoelectric materials ScP and ScAs, which are stretchable up to 14%, stable up to 700 K, and can have lattice thermal conductivity as low as 0.45 W m −1 K −1 . Abstract : We present two newly designed two-dimensional (2D) thermoelectric materials ScP and ScAs, which are stretchable up to 14% as well as dynamically and thermally stable up to 700 K. From a systematic study using density-functional calculations, ab initio molecular dynamics simulations and phonon studies, we find that these compounds are narrow band gap semiconductors and crystallize in a puckered structure, as is the case for many experimentally realized 2D materials like phosphorene and arsenene. The transport properties of these compounds are estimated using the semi-classical Boltzmann transport approach. The lattice thermal conductivity ( k l ) in the unstrained system is estimated to be 8.3 and 5 W m −1 K −1 for ScP and ScAs respectively which are less compared to those of pristine phosphorene (24–110 W m −1 K −1 ) and arsenene (6–30 W m −1 K −1 ). Furthermore, the k l of these compounds becomes ultra-low (∼0.45 W m −1 K −1 ), when they are subjected to optimum tensile strain conditions. Highly dispersed bands of ScP and ScAs, due to strong p–d hybridization, give rise to large electrical conductivity (∼10 8 S m −1 ) which is two orders higher than that of arsenene and phosphorene. The strain also brings nearly a two- and three-fold increase in the Seebeck coefficient with respect to the unstrained value in these compounds. Overall, the strain tunable large figure of merit (∼0.65–0.9) makes these compounds promising thermoelectric materials.